Performance properties of irradiated recycled polypropylene as a compatibilizer in recycled polypropylene/microcrystalline cellulose composites - Samat, Noorasikin; Lazim, Nurul Hakimah; Motsidi, Siti Nor Rasyidah; Hassan, Noor Azlina (Trans Tech Publications, Switzerland, 2017)
Effects of irradiated rPP compatibilizer, on the mechanical and thermal properties of recycled polypropylene/microcrystalline cellulose composites (rPP/MCC), are investigated. rPP is irradiated with an electron beam at dosages ranging from 10, 20, 30 to 50kGy. A matrix, containing of unirradiated and irradiated rPP (50:50 by ratio), is then added to 5, 20 and 40wt% MCC fibres. The composites are prepared using a twin screw extruder, followed by injection moulding. The properties are then characterized using tensile and thermal degradation tests. The improvement of Young’s modulus by up to about 45% suggests a compatibilising effect of the irradiated rPP. Fracture surface observations reveal an adhesion between rPP matrix and MCC fibres. However, the thermal stability deteriorated with the addition of MCC and irradiated rPP.